Advantages, disadvantages and risks in the adoption of design-build contracting method in the Brazilian public sector - Albuquerque, Ana Elisabete Cavalcanti; Primo, Marcos André de Mendes; Pereira, Felipe Augusto (Review of Business Management, 2015)
Objective – This paper aims to identify advantages, disadvantages and risks involved in the adoption of design-build contracting method in the Brazilian public sector. Design/methodology/approach – qualitative case study, in which were made documentary and field research in the form of semi-structured interviews. About the documentary and field data was used content analysis and triangulation of sources and collection methods. Findings – The theoretical basis of this research lies in the brazilian legislation for contracting works and studies conducted by various authors in which address the advantages of design-build procurement method (a single contract for design and construction) regarding the design-bid-build method used in Brazil, which hires design and construction separately. Practical implications – The research identified advantages, disadvantages and risks associated to the adoption of the design-build method , enabling the development of coping strategies if it is deployed. Originality/value – managers aware of these aspects could use coping strategies by adopting measures to reduce or eliminate their effects. The results can contribute not only to a possible implantation of the method in contexts even other than the public sector but also to improve the processes regarding the project and execution of works.